History - Nia, Sonia S; ., Djakariah; Dethan, Delsy A. (Universitas Nusa Cendana, 2022)
ABSTRACT History of theentery of the Butonese Ethnicity ini Sagu Vilalage on Adonara Island in 1894-1930. In Sagu Village, Adonara District, East Flores Regency. The problems in this research are (1) What it the history of the arrival of the Butonese etnic group in Sagu Village on Adonara Island in 1894-1930. (2) What is the social, cultural and economic development of the Butonese ethnic group in Sagu Village. The technique for determining informants was carried out using snowball sampling. The data sources used were primary data sources, secondary data sources and document studiea. The data collection techiques. The research results showed that (1) During the regain of King Arkian Kamba in 1894-1930, the Butonese ethnic community began to settle because a family from the Buton Sultanate namaed Bapa Haji Lama Kida come ti propose to King Arkian Kamba first daughter Ema Siti Kadija. So they settled in Sago Village until now. (2) Initially, the Butonese people who came did now know about dowry in local terms called belis, in the form elephant ivory whch is common among the Lamaholot tribe, now the also use the dowry. The Butonese ethnic group entered Sago Village at that time not only to trade but they also strated to spread Islam. The skills of the Butonese people who are good at sailing are still practiced people who are good at saling are still practiced today, even if they are just cetching fish. Keywords: History, Society, Ethnicity